2007
DOI: 10.1182/blood.v110.11.1557.1557
|View full text |Cite
|
Sign up to set email alerts
|

Del(6)(q22) and BCL6 Rearrangements in Primary Central Nervous System Lymphoma (PCNSL) Are Indicators of an Aggressive Clinical Course.

Abstract: Purpose: Despite therapeutic advancements, biological markers that predict the natural history of primary central nervous system lymphoma (PCNSL) are lacking and age and performance status are the only consistently identified independent prognostic variables. BCL6 rearrangements and deletion of the tumor suppressor gene R-PTP-κ (PTPRK) at 6q22 are thought to be common genetic abnormalities in PCNSL but their prognostic significance is unknown. The aim of this study is to determine the prevalence and survival i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Patient‐specific therapy is difficult to achieve because little is known regarding the molecular pathogenesis of PCNSL. This study confirmed our earlier observation that deletion of the 6q22‐23 region correlated with shorter survival of PCNSL patients, suggesting a biological region of interest (Cady et al , 2008). The study reported here comprised newly diagnosed PCNSL patients enrolled in three successive phase II clinical trials conducted by the NCCTG.…”
Section: Patient Cohorts By Ncctg Trial Numbersupporting
confidence: 91%
See 2 more Smart Citations
“…Patient‐specific therapy is difficult to achieve because little is known regarding the molecular pathogenesis of PCNSL. This study confirmed our earlier observation that deletion of the 6q22‐23 region correlated with shorter survival of PCNSL patients, suggesting a biological region of interest (Cady et al , 2008). The study reported here comprised newly diagnosed PCNSL patients enrolled in three successive phase II clinical trials conducted by the NCCTG.…”
Section: Patient Cohorts By Ncctg Trial Numbersupporting
confidence: 91%
“…Based on our earlier observation that deletion of chromosomal region 6q22‐23 correlated with shorter survival of primary central nervous system lymphoma (PCNSL) patients (Cady et al , 2008) the overall goal of this study was to further refine the biomarker potential of 6q22‐23. We now describe the correlation of its deletion with the overall survival (OS) of patients enrolled on three consecutive North Central Cancer Treatment Group (NCCTG) Phase II clinical trials for newly diagnosed PCNSL, 867252 (O’ Neill et al , 1999), 937351 (Laack et al , in press), and 967351 (Laack et al , 2006).…”
Section: Patient Cohorts By Ncctg Trial Numbermentioning
confidence: 99%
See 1 more Smart Citation